2017
DOI: 10.1039/c7se00086c
|View full text |Cite
|
Sign up to set email alerts
|

Template-free synthesis of mesoporous manganese oxides with catalytic activity in the oxygen evolution reaction

Abstract: Porous manganese carbonate was obtained via solvothermal synthesis using ethanol and urea. The manganese carbonate was subsequently used as a precursor to synthesise mesoporous manganese oxides via thermal treatments at three various temperatures. X-ray diffraction and Extended X-ray Absorption Fine Structure (EXAFS) results shows that g-MnO 2 is synthesised at 380 and 450 C while Mn 2 O 3 is produced at the annealing temperature of 575 C. X-ray absorption spectra show that g-MnO 2 converts completely to Mn 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 69 publications
3
34
0
Order By: Relevance
“…Nakamura and coworkers [44,45] discuss that more Mn 3+ ions lead to higher activity, which is in line with the e g orbital descriptor proposed by Suntivich et al [47]. In their catalytic model, comproportionation of Mn 4+ serves as a secondary supply of the catalytically active Mn 3+ , which may explain that the lowest overpotential in systematic studies of the OER on simple manganese oxides is usually found for mixed Mn 3+/4+ oxides [3,4,[38][39][40]42]. Therefore, it is critical to control the distribution of Mn cations in Mn-based electrocatalysts for the OER to understand their activity and potential degradation.…”
Section: Introductionsupporting
confidence: 57%
See 2 more Smart Citations
“…Nakamura and coworkers [44,45] discuss that more Mn 3+ ions lead to higher activity, which is in line with the e g orbital descriptor proposed by Suntivich et al [47]. In their catalytic model, comproportionation of Mn 4+ serves as a secondary supply of the catalytically active Mn 3+ , which may explain that the lowest overpotential in systematic studies of the OER on simple manganese oxides is usually found for mixed Mn 3+/4+ oxides [3,4,[38][39][40]42]. Therefore, it is critical to control the distribution of Mn cations in Mn-based electrocatalysts for the OER to understand their activity and potential degradation.…”
Section: Introductionsupporting
confidence: 57%
“…Yet, small amounts of Mn 2+ and Mn 4+ are beneficial if Mn comproportionation of these ions to Mn 3+ is possible on the surface of the Mn oxide [44,45]. Thus, the lowest overpotential in systematic studies of the OER on manganese oxides is usually found between Mn 3.5+ and Mn 3.7+ [3,4,[38][39][40]42], rather than Mn 3+ . Nonetheless, materials with mainly Mn 4+ perform significantly worse than those with sizable amount of Mn 3+ , e.g.…”
Section: Samplementioning
confidence: 99%
See 1 more Smart Citation
“…Further discussion of chemical stability toward ageing of many of the oxide materials reported would also be recommended. Most of the highly active oxide materials are disordered, porous and highly defective, therefore chemical ageing effects are likely to be important; in our own work on MnO x for the OER we have noted how structural changes in highly disordered phases can lead to activity loss [47] . A better understanding of structural instability and its undesirable but also desirable effects, as outlined in [48] , would be thus beneficial.…”
Section: Discussionmentioning
confidence: 98%
“…For manganese oxides, the electrochemical and physicochemical properties are highly dependent on morphology and crystallographic nature [173][174][175][176][177][178][179][180]. Therefore, to study the effects of structure on OER activity, Meng et al [177] synthesized four different crystal lattices of MnO 2 , including α, β, σ-MnO 2 and amorphous MnO 2 (AMO), and analysed them. Here, XRD patterns confirmed the amorphous nature of the AMO with three weak peaks and SEM images revealed aggregated particles of less than 50 nm.…”
Section: Mn Oxidesmentioning
confidence: 99%